2020
DOI: 10.1186/s12889-020-08646-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment success and mortality among adults with tuberculosis in rural eastern Uganda: a retrospective cohort study

Abstract: Background Successful treatment of tuberculosis leads to clinical and public health benefits such as reduction in transmission, complications, and mortality among patients. However, data are limited on treatment outcomes and the associated factors among persons with bacteriologically confirmed pulmonary (BC-PTB) in rural areas of high dual tuberculosis and Human Immunodeficiency Virus (HIV) burden countries such as Uganda. We investigated factors associated with successful treatment of tuberculosis and mortali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
12
13
0
1
Order By: Relevance
“…TB and HIV diagnosis have also been associated with stigma, which might further have adverse effects on TB treatment outcomes [50,51]. Like our study, a number of previous studies have found HIV association with poor TB treatment outcomes [52][53][54]. Surveillance systems like the one in place in our setting should play a key role in providing data for action.…”
Section: Discussionsupporting
confidence: 56%
“…TB and HIV diagnosis have also been associated with stigma, which might further have adverse effects on TB treatment outcomes [50,51]. Like our study, a number of previous studies have found HIV association with poor TB treatment outcomes [52][53][54]. Surveillance systems like the one in place in our setting should play a key role in providing data for action.…”
Section: Discussionsupporting
confidence: 56%
“…TB and HIV diagnosis have also been associated with stigma, which might further have adverse effects on TB treatment outcome [29,30]. Like our study, a number of previous studies have found HIV association with poor TB treatment outcomes [31][32][33].…”
Section: Discussionsupporting
confidence: 66%
“…Our data show that among HIV-negative people with TB, long distance was associated with a lower risk of mortality, but among those with TB/HIV, there seemed to be a higher risk for mortality for those traveling longer distances although the relationship did not reach statistical significance. The data suggest that longer distances affect people with TB/HIV more than those without HIV, probably due to complex interaction between HIV and TB, with each disease influencing the other's progression, severity, and response to treatment [26] , [27] , notwithstanding travel distance. Besides, people with TB/HIV who have difficult access to health facilities do not comply with TB treatment [28] and this exacerbates their risk of mortality [29] , [30] .…”
Section: Discussionmentioning
confidence: 96%